Mesotrione Activity on Crabgrass (Digitaria spp.) as Influenced by Nitrogen Fertilization Rate, Source, and Timing. (June 2015) - Beck, Leslie L.; Patton, Aaron J.; Law, Quincy D.; Weisenberger, Daniel V.; Brosnan, James T.; Almodóvar, José J. Vargas; Breeden, Gregory K.; Kopsell, Dean A.
Abstract : Mesotrione, a 4-hydroxyphenylpyruvate dioxygenase-inhibiting herbicide, is labeled for PRE and POST crabgrass control. It has enhanced efficacy on smooth and large crabgrass when applied in conjunction with soil-applied nitrogen (N). The objectives of this study, using crabgrass as the weed species, were to (1) determine the influence of N rate and tissue N concentration on mesotrione activity, (2) determine the influence of N source on mesotrione activity, and (3) determine the influence of N application timing on mesotrione activity. Large crabgrass plants that received 12 kg N ha −1 or more before mesotrione application had more bleached and necrotic leaves compared with plants that received 0 kg N ha −1 7 d after treatment (DAT) in the greenhouse. Although N application rates as high as 98 kg N ha −1 were tested, 90% leaf bleaching and necrosis were observed with rates of 8.9 or 10.1 kg N ha −1 in Tennessee and Indiana, respectively. Nitrogen concentration in large crabgrass leaf and stem tissue on the day of the mesotrione application was closely related to the bleaching and necrosis symptoms observed 7 DAT. Although N rate influenced mesotrione activity, N source did not. Nitrogen application timing was also important, with N applications 3, 1, and 0 d before a mesotrione application having the highest percentage of bleached and necrotic leaves in greenhouse experiments. Both greenhouse and field trials support the finding that N applications in proximity to the mesotrione application enhance herbicide activity. Thus, practitioners can pair N and POST mesotrione applications together or in proximity to enhance crabgrass control.